Perancangan Model CRM Emosional pada Bisnis Optik di Yogyakarta Berbasis Historis Kesehatan Mata (Studi Konseptual dan Prototipe) - Arraywed Wibowo; Sri Wahyu Budoyo Kusumo; Ardhitya Furqon Wicaksono; Levya Otivian Nuvida (Fakultas Ekonomi dan Bisnis Islam, 2025)
Abstract The rapid digital transformation in the healthcare industry has significantly reshaped how optical businesses engage with their customers. Traditional Customer Relationship Management (CRM) models, which primarily emphasize transactional interactions, are increasingly viewed as insufficient in fostering sustained customer loyalty. This study proposes the design of an emotional CRM framework that leverages historical eye health data to create personalized, proactive, and emotionally resonant customer experiences. Growing public awareness of visual health offers a strategic opportunity for innovation in customer engagement practices within the optical sector, which has traditionally focused more on product offerings and direct sales. The methodology employed combines a systematic literature review of 45 academic publications spanning 2018 to 2024 with a design thinking approach to develop a prototype of an emotional CRM system. This system utilizes a customer’s eye examination history to deliver periodic reminders, personalized lens recommendations based on evolving visual conditions, and emotionally supportive messages tailored to individual needs. Findings indicate that the emotional CRM model significantly enhances customer loyalty through increased repeat visits and deeper emotional connection to the optical brand. Moreover, the model boosts customer satisfaction by offering personalized health-focused interactions, thus moving beyond conventional sales-based services. The study concludes that integrating eye health data into CRM systems facilitates a more holistic, patient-centered, and long-term service model. Recommendations include the development of secure and ethically-managed integrated information systems, the training of personnel in empathetic communication strategies, and the reinforcement of data protection policies specific to the optical services industry. Keywords:emotional CRMoptical businesseye health historyinformation systemcustomer loyalty